NLRC5 overexpression in ovarian tumors remodels the tumor microenvironment and increases T-cell reactivity toward autologous tumor-associated antigens - Rodriguez, Galaxia M.; Yakubovich, Edward; Murshed, Humaira; Maranda, Vincent; Galpin, Kristianne J.C.; Cudmore, Alison; Hanna, Andrew M. R.; Macdonald, Elizabeth; Ramesh, Shashankan; Garson, Kenneth; Vanderhyden, Barbara C. (Frontiers in Immunology, 2024)
Epithelial ovarian cancer (OC) stands as one of the deadliest gynecologic malignancies, urgently necessitating novel therapeutic strategies. Approximately 60% of ovarian tumors exhibit reduced expression of Major Histocompatibility Complex class I (MHC I), intensifying immune evasion mechanisms and rendering immunotherapies ineffective. NOD-like receptor CARD domain containing 5 (NLRC5) transcriptionally regulates MHC I genes and many antigen presentation machinery components. We therefore explored the therapeutic potential of NLRC5 in OC. First, we generated OC cells overexpressing NLRC5 to rescue MHC I expression and antigen presentation, and then assessed their capability to respond to PD-L1 blockade and an infected cell vaccine. Analysis of microarray datasets revealed a correlation between elevated NLRC5 expression and extended survival in OC patients; however, NLRC5 was scarcely detected in the OC tumor microenvironment. OC cells overexpressing NLRC5 exhibited slower tumor growth and resulted in higher recruitment of leukocytes in the TME with lower CD4/CD8 T cell ratios, and increased activation of T cells. Immune cells from peripheral blood, spleen, and ascites from these mice displayed heightened activation and interferon-gamma production when exposed to autologous tumor-associated antigens. Finally, as a proof-of-concept, NLRC5 overexpression within an infected cell vaccine platform enhanced responses 2 This is a provisional file, not the final typeset article and prolonged survival in comparison to control groups when challenged with parental tumors. These findings provide a compelling rationale for utilizing NLRC5 overexpression in "cold" tumor models to enhance tumor susceptibility to T cell recognition and elimination by boosting the presentation of endogenous tumor antigens. This approach holds promise for improving antitumoral immune responses in OC.